The new concept of the book between rationalization and granularity - Živković, Daniela (2003)
The traditional book sector and three basic professions - publishing, librarianship and the book trade - are based on the concept of the physical copy of a book. In the second half of the twentieth century technological development made it possible to publish books on media other than paper. This resulted in changes in the size and equipment of books, and the classification of what was and what was not a book according to number of pages began to complicate book management. There is an increasing need for a new definition of "book" that would reflect the changes that have already taken place in size and medium, and indicate future development. The author's purpose is to revise the definition of the book. She based her research on the application of ISBN, the International Standard Book Numbering System, in 27 countries all over the world. Emphasis is now laid on a work of monographic character with the function of a book published in any medium. The author also gives the definition of the electronic book. The basic principle of traditional publishing is first to publish a title and then distribute it, but the introduction of contemporary technology has reversed this order because an online electronic book can first be distributed and then downloaded, printed out or even printed on demand. The possibility of publishing electronic works, their online transfer and finally digital printing has created a book to fit the reader. The advent of the electronic book and other electronic material has therefore placed before librarians many issues in connection with how to organise the basic functions of libraries. There is a need to introduce new courses like electronic publishing into the curricula of library and information schools in order to discuss the latest forms of publishing and stress the cooperation of publishers and librarians. Recent international development in copyright and other legal matters in the electronic environment call for intensified courses dealing with legal aspects of librarianship.